The Role of Gut Microbiota in Pediatric Obesity: A Systematic Review and Meta Analysis of Microbiota Profiles in Obese versus Normal Weight Children - Karina Fitria Alhaq; Fayyaza Faiz Adams; Athifah Nur Azizah Arif; Pricilia Laurenza Salsabila; Filla Reviyani Suryaningrat (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Pediatric obesity is increasingly acknowledged as a significant public health issue with the gut microbiome identified as a potential contributing factor. Increasing evidence indicated that the gut microbiome is integral to metabolic health and the etiology of obesity. Nonetheless, data pertaining specifically to pediatric populations is still limited and underexplored. This study compared the composition of gut microbiota between obese and normal-weight children and to identify microbial patterns associated with pediatric obesity. Methods: This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A thorough literature search was performed across various databases. We looked at eligible studies and then rated their quality and analyzed them with Newcastle–Ottawa Scale (NOS) and Review Manager (RevMan) 5.4. Result: This systematic review and meta-analysis included ten studies involving 562 children, utilizing cross-sectional and case-control methodologies. The meta-analysis, which included two studies with 124 participants (64 obese and 60 normal-weight), showed that the Firmicutes to Bacteroidetes (F/B) ratio was much higher in obese children than in normal-weight (mean difference = 5.15; p < 0.00001). Taxonomic analysis showed obese children had more members of the phylum Firmicutes, such as Lactobacillus, Clostridium, and Megamonas. On the other hand, Bacteroidetes, especially Prevotella and Bacteroides, were usually less abundant. Conclusion: The results indicate that dysbiosis in gut microbiota may contribute to pediatric obesity. These results underscore the potential of gut microbiota modulation as a treatment for childhood obesity. Research is necessary to clarify causal mechanisms and investigate microbiota-based-interventions.